1999
DOI: 10.1099/00222615-48-5-479
|View full text |Cite
|
Sign up to set email alerts
|

Some immunological properties of lipopolysaccharide from Acinetobacter baumannii

Abstract: Acinetobacter baumannii, mainly biotype 9, is an important nosocomial opportunist pathogen in Chile and other countries. The biological basis of its virulence and prevalence is still unknown. As lipopolysaccharide (LPS) is often associated with virulence, some biological properties of purified LPS from seven nosocomial isolates, comprising four isolates of A. baumannii biotype 9, two isolates of biotype 8 and one isolate of biotype 1, were investigated. LPS was extracted and purified from each isolate by the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…LPS from A. baumannii induces inflammatory cytokines, such as IL-8 and tumor necrosis factor (TNF), from mouse splenocytes and human macrophages at levels equivalent to those stimulated by LPS from Escherichia coli (122,123). The LPS activates cytokine production in a manner requiring TLR4, whereas whole A. baumannii is able to activate cytokines via both TLR4 and, for unclear reasons, TLR2 (123).…”
Section: Immunological Defense Mechanismsmentioning
confidence: 99%
“…LPS from A. baumannii induces inflammatory cytokines, such as IL-8 and tumor necrosis factor (TNF), from mouse splenocytes and human macrophages at levels equivalent to those stimulated by LPS from Escherichia coli (122,123). The LPS activates cytokine production in a manner requiring TLR4, whereas whole A. baumannii is able to activate cytokines via both TLR4 and, for unclear reasons, TLR2 (123).…”
Section: Immunological Defense Mechanismsmentioning
confidence: 99%
“…Prevalence of certain biotypes suggests that those micro-organisms have special properties or factors. Work in this laboratory has demonstrated that nosocomial isolates of A. baumannii produce a smooth-type LPS (S-LPS), and this macromolecule might contribute to pathogenicity [3]. Furthermore, many strains of Acinetobacter are capsulate and the capsular polysaccharide (CPS) might be associated with protection of bacteria from phagocytosis and complement [2].…”
Section: Introductionmentioning
confidence: 99%
“…Spleen cell suspensions were obtained and challenged with 10 ìg of LPS as described above, but for a period of 24 h. The stimulated cells were concentrated by low speed centrifugation as described previously [24] and TNF-AE was determined in the supernates of cell cultures by a Mouse TNF-AE ELISA kit (BioSource International, Camarillo, USA), according to the manufacturer's instructions. Positive and negative controls were the same as those used for B-cell proliferation assays.…”
Section: Tnf-ae Determinationmentioning
confidence: 99%
“…Blastogenic response was evaluated by the ability of LPS to induce spleen growth, expressed as a splenic index ¼ [spleen weight (g)=mouse weight (g)] 3 1000 [24]. Briefly, groups of four female mice were inoculated intraperitoneally with 10 ìg of LPS and killed after 4 days by cervical dislocation to allow extraction of the spleen.…”
Section: Splenic Indexmentioning
confidence: 99%